1999
DOI: 10.1115/1.483274
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Simulation of Fish-Inspired Unsteady Vortex Dynamics on a Rigid Cylinder

Abstract: The unsteady hydrodynamics of the tail flapping and head oscillation of a fish, and their phased interaction, are considered in a laboratory simulation. Two experiments are described where the motion of a pair of rigid flapping foils in the tail and the swaying of the forebody are simulated on a rigid cylinder. Two modes of tail flapping are considered: waving and clapping. Waving is similar to the motion of the caudal fin of a fish. The clapping motion of wings is a common mechanism for the production of lift… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…Bandyopadhyay et al [10] study a streamlined vehicle equipped with two flapping foils in close proximity. Force and efficiency measurements and flow visualization results, show strong interaction effects that require more parameters than the ones used for single foils.…”
Section: Multiple Foils and Foils Interacting With Bodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Bandyopadhyay et al [10] study a streamlined vehicle equipped with two flapping foils in close proximity. Force and efficiency measurements and flow visualization results, show strong interaction effects that require more parameters than the ones used for single foils.…”
Section: Multiple Foils and Foils Interacting With Bodiesmentioning
confidence: 99%
“…The efficiency was up to 58% for angular amplitude of 15 , lower for other conditions. Bandyopadhyay et al [9], [10] employed two foils flapping against a middle flat plate. They report efficiencies up to 30%, while the vortical patterns form a rapidly expanding wake.…”
Section: Multiple Foils and Foils Interacting With Bodiesmentioning
confidence: 99%
“…In the next section, a dorsal fin device for brisk maneuvering based on the result in Figure 2, is examined in the context of a rigid cylinder having a large aspect ratio. Bandyopadhyay et al (2000a).…”
Section: Low-speed Maneuvering Dynamics Of Fish and Small Underwater mentioning
confidence: 99%
“…Regarding the development of biomimetic multiple propulsors system, Bandyopadhyay et al [15] investigated the swimming hydrodynamics of a pair of flapping foils to the tail of a rigid body. Akiyama et al [16] observed that flow fields around vibrating plates created counter rotating vortices.…”
Section: Introductionmentioning
confidence: 99%